2017
DOI: 10.1002/cne.24263
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of IGF‐I system in neurons of the inflamed spinal cord during acute experimental autoimmune encephalomyelitis

Abstract: There is growing evidence that the impaired IGF-I system contributes to neurodegeneration. In this study, we examined the spinal cords of the EAE, the animal model of multiple sclerosis, to see if the expression of the IGF-I system is altered. To induce EAE, C57/BL6 mice were immunized with the Hooke lab MOG kit, sacrificed at the peak of the disease and their spinal cords were examined for the immunoreactivities (ir) of the IGF-I, IGF binding protein-1 (IGFBP-1) and glycogen synthase kinase 3β (GSK3β), as one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…IGFBP7 is released by senescent cells, and cellular senescence is a pathway we previously identified as activated in HD-MSNs with a multitude of relevant markers, including IGFBP7 mRNA ( 60 ). IGFBPs are biomarkers for multiple diseases, and their expression causes neurodegeneration ( 61 , 62 , 63 , 64 , 65 , 66 , 67 ). Western blot analysis further validated the increased levels of IGFBP7 in HD72-MSNs ( supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IGFBP7 is released by senescent cells, and cellular senescence is a pathway we previously identified as activated in HD-MSNs with a multitude of relevant markers, including IGFBP7 mRNA ( 60 ). IGFBPs are biomarkers for multiple diseases, and their expression causes neurodegeneration ( 61 , 62 , 63 , 64 , 65 , 66 , 67 ). Western blot analysis further validated the increased levels of IGFBP7 in HD72-MSNs ( supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings of vitronectin as favorable compared to the control (Figure 2 and Figure 4) was thus not unexpected. Recent studies have also shown that intraventricular administration of IGF-1 after experimental traumatic brain injury results in the enhanced generation of immature hippocampal neurons in the granular layer of the dentate gyrus [11] and that an impaired IGF-1 system contributes to neurodegeneration in inflammatory disorders in CNS [34]. These findings could support the notion that IGF-1 is of importance in CNS injuries, even though the picture is far from fully understood regarding the fine tuning of the IGF/IGFBP/vitronectin complex in the nervous system.…”
Section: Discussionmentioning
confidence: 99%